Menyikapi Pluralisme Agama Perspektif Al-Qur’an - Azhari Andi; Ezi Fadilla (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Nowadays, the discourses of religion pluralism is one of the frequently-discussed issue among muslim. This case appears along with the emergence of books, works, writings in the mass media, congress, seminars, discussions, and dialogue which are focusing on the religion pluralism. One of the factors causing the emergence of this discourse is a number of conflicts that happened among different religious adherents which was often began by an excessive truth claim. The discourse presented in this paper aims to create harmony life and peace among different religion adherents. Al-Qur’an both admits the existence of other religions and commands its followers to live in harmony as well as respect each other. Islam is “rahmah lil ’ālamīn”, but yet the reality that happens in muslim world is not in line with the ideality. So the question arises in our minds; where is Islam as rahmah lil ’ālamīn? the fact is there are still many muslim who can’t wisely face the plurality as it has been taught by the Qur’an. So how is the Qur’anic guidance to face the plurality? Based on this reason, this article would like to discuss on the Qur’anic guidance in facing the religion pluralism using descriptive-analysis method.[Dewasa ini, wacana tentang pluralisme agama merupakan isu yang sangat hangat diperbincangkan, terutama di kalangan muslim. Hal ini bisa dilihat dari lahirnya buku-buku, karya-karya, tulisan-tulisan di media masa, kongres, seminar- seminar, diskusi, dan dialog-dialog yang membahas tentang pluralime agama. Faktor yang melatarbelakangi munculnya wacana ini antara lain adalah konflik-konflik yang marak terjadi antar umat beragama yang sering kali bermula dari klaim kebenaran yang berlebihan. Wacana ini bertujuan untuk mewujudkan kerukunan dan perdamaian antar umat beragama. al-Qur’an sendiri mengakui keberadaan agama-agama lain dan menyeru umatnya agar hidup berdampingan dan saling menghormati antar sesama. Islam datang sebagai rahmah lil’almin, namun realitas yang terjadi tidak singkron dengan idealitas. Lalu timbul pertanyaan, di manakah letak Islam yang rahmah lil’alamin itu? Faktanya, disana sini banyak umat Islam yang tidak bisa menyikapi keanekaragaman dengan bijaksana, sebagaimana yang diajarkan dalam al-Qur’an. Lalu bagaimanakah tuntunan al-Qur’an untuk menyikapi perbedaan? Berdasarkan itu, tulisan ini akan mendiskusikan tentang tuntunan al-Qur’an dalam menyikapi pluralisme agama dengan metode deskriptif-analitis.]